RUSSIAN-LANGUAGE LITERATURE OF BELARUS: EXPANSION OR TRADITION OF MULTICULTURALISM? - Kavalou, Siargey (Porównania, 2014)
More and more publications devoted to the phenomenon of „multilingualism” in Belorussian literature are appearing nowadays.This fact is highly connected with the intensive development and the problem of Russian-language literature’s national identity in modern Belarus in an attempt to answer the question: what culture – Russian or Belarusian – does it belong to? Another important problem is whether modern Russian-language literature of Belarus harms the development of literature in Belarus? Detailed research of this question shows that it is not the Russian-language literature that is harmful, but social, political and economic conditions in which both elements exist and which support the development of the Russian-language art in Belarus: expulsion of Belarusian language from the sphere of active use to the phere of the cultural reservations, identification of non-state publications as the ones that resist state policy, powerful influence of the Russian book market, etc.